PENGARUH DOLOMIT DAN PUPUK P TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L.) SEBAGAI TANAMAN SELA DIANTARA KELAPA SAWIT DI LAHAN GAMBUT - Fitria Darpis; Nelvia Nelvia; Islan Islan (DINAMIKA PERTANIAN, 2017)
The research aims to study the interaction of dolomite dose and P fertilizer application on growth and yield of peanut plants as intercropped between palm oil on peatland. The study was conducted in the agriculture experimental station Faculty of Agriculture, University of Riau, Rimbo Panjang village, Kampar District, from December 2015 to April 2016. The research utilizes a Randomized Complete Block Design (RCBD), which consists of two factors. The first factor is dolomite consists of 3 levels (0, 500 and 1000 kg/ha) and second factor P fertilizer consists of 4 levels (0, 23, 46 and 69 kg P2O5/ha), each combination has 4 replication. The parameters observed were plant height, number of primary branches, flowering age, harvesting age, number of pods, number of seeds per pods, the weight of dry seeds and filled seeds/m2, percentage of filled seeds, the weight of 100 seeds. The data of each parameter were analyzed with analysis of variance (ANOVA) followed by Duncan's New Multiple Range Test (DNMRT) at 5% level. The results showed that the increase of weight of dry seeds and filled seeds /m2were significant at the application of 69 kg P2O5/hafollowed by 500 kg dolomite/ha and percentage of filled seeds at the application of 69 kg P2O5/hafollowed by 1000 kg dolomite/ha compared to without P fertilizer and dolomite, whereas in plant height, number of primary branches, flowering age, harvesting age, number of pods, number of seeds per pods and weight 100 seeds were not significant each combination of treatments.